MARKETING STRATEGIES FOR ROMANIAN TRADITIONAL PRODUCTS - Iuliana CETINA; Dumitru GOLDBACH; NataliaMANEA; Loredana POPESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article presents the main agro-food marketing strategies (product, price, placement, promotion) based on two researches (qualitative among producers and key decision makers, and quantitative among urban consumers) in South Muntenia Region. The main objective of the research was to determine the extent to which the small traditional producers have the willingness to group together in an associative form. The research shows that traditional manufacturers encounter barriers to the valorisation-marketing of products to end-users. At the same time, urban propensity to traditional products has been reported. Based on the conclusions drawn from the qualitative research, a model has been developed that includes the main dimensions of sustainable development (economic, ecological, social and cultural dimension). Qualitative research has led to the hypotheses for quantitative research, which was based on a questionnaire consisting of dichotomic and multichatal questions. Following the research, a set of strategies were proposed to support traditional producers. Research has been limited to the South-Muntenia area, with research being extended at national level in the future.